Analisis Kelelahan Kerja Yang Berpotensi Terjadinya Kecelakaan Kerja Pada Nelayan di Wilayah Pesisir - Nurly Fadila; Mutiara Ashifa; Fatma Salsabila; Susilawati; Abdurrozzaq Hasibuan (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Fishermen are a group of humans who put their hope in the product of the sea. Fatigue experienced by fishermen can result in reduced performance and loss of security, thus endangering the fishermen and others. This literature study aims to obtain information and analyze a burgeoning article with potential work exhaustion against fishermen's work accidents. The methods used to collect information are the methods of literature view through online media sources such as Mendeley, Google Schoolar, publication or publication, and other online media. Based on the articles already collected results, there's a factor contributing to work accidents for fishermen, one of which is work fatigue. Fatigue can cause a drop in awareness of safety and health at work for fishermen and psychosomatic abilities. Fishermen who worked in tired conditions were more likely to have work accidents.